SALTED FISH PRESERVATION MENGGUNAKAN HERBS EDIBLE COATING DARI NANOPARTIKEL BAWANG PUTIH, DAUN PANDAN DAN SERAI DAPUR - Doktorasaintifika, Heradita Kaniaazzahra; Nurkertamanda, Denny; Shasabila, Analies Devi; Kusumaningrum, Hermin Pancasakti; Sugiarti, Lilis; Wahyuningsih, Candra; Herida, Azalia Puspa; Hapsari, Hererapratita Aysha (Cendekia Journal of Pharmacy, 2025)
Global consumption trends show a tendency to choose natural food preservatives, especially those derived from plants, especially to avoid chemical and synthetic preservatives that are harmful to health. Nanotechnology is an important development and an efficient choice to extend the shelf life of food. This study aims to create and carry out seafood preservation using herbs edible coating from garlic nanoparticles, pandan leaves and lemongrass to determine its use as a preservative for salted mackerel and tigawaja salted fish. As a comparison, a mixture of the three ingredients. The study used four treatments where each was repeated 3 times. A hedonic test was also carried out in the form of observations of dryness, color, texture and odor of salted fish. The research method consisted of making garlic nanoparticle extract, pandan leaf extract, lemongrass extract, and a mixture of the three ingredients followed by microscopic observation. Antibacterial activity was carried out using the TPC test. The hedonic test was carried out to see the potential of consumers for the product. Furthermore, a PASS analysis was carried out to see the potential of antimicrobial compounds in the three ingredients. The results showed that the edible coating layer was made into nanoparticle form. Edible coating from pandan is most suitable for use on salted mackerel. Edible coating from garlic is most suitable for use on tigawaja salted fish. The TPC test results showed that garlic, pandan and lemongrass were able to prevent microbial growth effectively for 48-96hours and have the potential to be used as edible coating.